Premarital Counseling: The Influence of Islamic Religious Counselors at Kua Kenjeran District to Educate the Culture of Early Marriage - Zarnuji, Aqib (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Every human being is born and created in pairs, and God has endowed humans with feelings of love, lust, and reason; besides that, it is human nature as social beings who cannot live alone. Marriage is a physical and spiritual bond between a man and a woman as husband and wife. Form a sakinah and eternal family based on the One and Only God. This study aims to determine the factors behind the occurrence of early marriage and provide an understanding to adolescents in KUA Kenjeran Regency on the psychological impact of early marriage. This study uses descriptive qualitative research methods. Observation, interviews, and documentation do data collection.